Role of Apoptotic Biomarkers in Ameloblastoma and Dental Follicle - Mashhadiabbas, Fatemeh; Safarpour, Roohallah; Ghorbani, Hakimeh (Journal of Dental School, 2021)
Objectives Ameloblastoma is an odontogenic neoplasm with locally aggressive behavior. Fas and FasL play important roles in apoptotic pathways. The aim of this study was to determine the possible role of expression of apoptotic pathways (Fas and FasL) in human ameloblastoma and the relationship of apoptosis with the clinical biological characteristics of ameloblastoma. Methods In this descriptive retrospective study, we investigated the anti-Fas and anti-FasL antibody expression in 11 dental follicles and 56 ameloblastoma specimens (35 conventional, 15 unicystic and 6 ameloblastic carcinoma samples) by immunohistochemical (IHC) staining and polymerase chain reaction (PCR). The percentage of positive cells was calculated by using the Mann-Whitney U test and Kruskal-Wallis test. Results The rate of expression of markers was significantly lower in dental follicles than all subtypes of ameloblastoma (P=0.01 for Fas, and P=0.0001 for FasL). The FasL proportional score was significantly higher in conventional ameloblastoma than in unicystic ameloblastoma and ameloblastic carcinoma (P=0.003). There was no significant relationship between the type of ameloblastoma and expression of Fas. Conclusion This study shows that the process of apoptosis in ameloblastomais a sign of behavioral change in odontogenic epithelial cells especially in conventional ameloblastoma and that the apoptotic factors may not play an effective role in the malignancy of ameloblastoma.